Barriers to embrace multidisciplinary learning experience in interior architecture design module / Norji Nasir and Kamal Rabah Mustapha Kamal - Nasir, Norji; Mustapha Kamal, Kamal Rabah (UiTM Press, 2024)
A multidisciplinary learning experience is an approach to curriculum integration which values the ideas of collaboration across multiple disciplines in response to the Fourth Industrial Revolution (4IR). The 4IR has effectively widened the division between fields in which graduates are expected to perform desired skill and knowledge. This paper aims to determine the barriers encountered by the Interior Architecture Students embracing the multidisciplinary learning experience with students from other discipline. Through an explanatory case study approach, the emergence of approach curriculum comprised of three programmes in the built environment at a private university will be presented. The paper concludes with reflective writing addressing the barriers faced by the Interior Architecture students during the multilearning experience. Findings of the study revealed the majority of students identify communication, time-management, responsibility, attitude, and teamwork as the most significant barriers encountered by Interior Architecture students in the implementation of the MLE approach in the Design Studio module. Developing strong communication skills, allocation in managing the time, team player roles and responsibility are essential trait that must be constantly fostered. These findings help to assist interior architecture educators in developing courses that integrate various disciplines and provide academics with a deeper understanding of the conceptualisations and practices of the multidisciplinary learning experience concept approach by identifying the barriers that hinder its implementation.